Temporomandibular joint examination reviewed - L. Guarda Nardini (PAGEPress Publications, 2001)
The temporo-mandibular joint (TMJ) it's a joint closely related to the skull base, the spine, and the jaws; all these anatomical structures must be taken in consideration when evaluating pain involving the tmj. In order to detect patients affected by pathology or dysfunctions of the tmj, physical examination is of great value in orienting the diagnosis. Inspection must consider the symmetry of the body, the dental status and the type of occlusion. Palpation is a way to assess contractiont involving the muscles of the masticatory system and of the neck. Auscultation, based on articular noise provides means to determine whether we are dealing with degeneration of the joint or a dislocation of the intrarticular disc. In order to confirm the diagnosis obtained with the clinical evaluation, it's useful to perform imaging techniques as opt, tomography and TC of the tmj and electromyokineosiography - index of the mandibular functionality and of the muscles status. MRI and dynamic MRI are among the non invasive exams which give the greatest amount of information, regarding the disc position and the joint degeneration. Arthroscopy is an invasive technique that allows early diagnosis of degeneration and is helpful to reveal early inflammatory processes of the joint.